Targeted dietary micronutrient fortification modulates n-3 LC-PUFA pathway activity in rainbow trout (Oncorhynchus mykiss) - Lewis, M.; Hamid, N.; Alhazzaa, Ramez; Hermon, K.; Donald, J.; Sinclair, A.; Turchini, G. (2013)
Replacing fish oil (FO) in aquafeeds with sustainable alternatives such as vegetable oils (VO) compromises the content of n-3 long-chain polyunsaturated fatty acid (n-3 LC-PUFA) in the edible portions of farmed fish. Endogenous biosynthesis of n-3 LC-PUFA from C18 precursors is catalysed by several enzymes, which have low activity in carnivorous fish. Rainbow trout were fed on VO-based diets supplemented with increasing levels of selected micronutrients as potential n-3 LC-PUFA biosynthesis co-factors or coenzyme precursors: iron, zinc, magnesium, niacin, riboflavin, pyridoxine and biotin at 100, 200, 300 or 400% of their recommended dietary inclusion. Providing the substrate (ALA, 18:3n-3) and the potential enzyme co-factors was assumed to enhance the efficiency of EPA (20:5n-3) and DHA (22:6n-3) production. Initial evidence was established when DHA and total n-3 LC-PUFA content increased in the whole body of fish from the treatment with the highest micronutrient fortification. Fewer changes were observed in the fillet or liver which was consistent with a marginal regulation of the mRNA expression of key biosynthesis genes in the liver. The potential co-factors seem to stimulate the n-3 LC-PUFA biosynthesis efficiency at the molecular and enzymatic level in rainbow trout fed on ALA-rich diet, leading to metabolic and chemical changes. The interactions between dietary substrate and enzyme co-factors/coenzymes need to be further investigated to advance lipid metabolism research and benefit the aquaculture industry. © 2013 Elsevier B.V.